First record of the genus Metacirolana sp. and Cymodoce tribullis (Crustacea; Isopoda) from South Andaman, Andaman Islands, India - Anil, Pathan; Ummath, Ameen; Mohammed PS, Bijin; Jayaraj, Kaderambil Arjunan (Journal of Tropical Life Science, 2020)
Isopoda are one of the most poorly known crustaceans in Andaman and Nicobar Islands. The present study has recorded genus Metacirolana sp. and Cymodoce tribullis, for the first time from South Andaman. This recent sighting provides a new distribution of this two species in the Indian province. The specimens were collected from the seaweeds of intertidal regions of Kodiyaghat, South Andaman, Andaman Islands. The morphological characteristics of these two species were described. Furthermore, this study adds two more species to the isopoda check list of Andaman and Nicobar Islands. The present study also provides additional information on epifaunal communities associated with the seaweeds in the intertidal region of Kodiyaghat, South Andaman.